Fashion branding and communication : core strategies of European luxury brands - Jin, Byoungho; Cedrola, Elena, 1965- (Palgrave Macmillan, 2017)
"This second volume in the Palgrave Studies in Practice: Global Fashion Management series focuses on core strategies of branding and communication of European luxury and premium brands. Brand is a critical asset many firms strive to establish, maintain, and grow. It is more so for fashion companies when consumers purchase styles, dreams and symbolic images through a brand. The volume starts with an introductory chapter that epitomizes the essence of fashion brand management with a particular emphasis on emerging branding practices, challenges and trends in the fashion industry. The subsequent five cases demonstrate how a family workshop from a small town can grow into a global luxury or premium brand within a relatively short amount of time. Scholars and practitioners in fashion, retail, branding, and international business will learn how companies can establish a strong brand identity through innovative strategies and management"--Zadní strana obálky
Keywords: obchodní značky -- Evropa; řízení značky -- Evropa; móda -- Evropa; luxusní zboží -- Evropa; marketing; brand name products -- Europe; brand management -- Europe; fashion -- Europe; luxuries -- Europe; případové studie; case studies